EFEKTIVITAS KERJA PEGAWAI DALAM MENERAPKAN E-OFFICE UNTUK MENDUKUNG E-GOVERNMENT DALAM KEGIATAN KORESPONDENSI KEDINASAN DI FAKULTAS EKONOMI UNIVERSITAS NEGERI SURABAYA - ULIMA RAHMAH, SHABRINA (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2015)
ABSTRACT Economics Faculty of State University of Surabaya has applied e-office in official correspondence activities effectively and work effectiveness of the employee has been good due to all the activities done electronically. In applying e-office, it is found that human resources must be expert in technology and commitment among the chief and all employees to give the best service as supporting factors. On the other hand, the inhabiting factors are unstable connection which is able to impede data process and also human errors which impede the application of e-office. Therefore, the use of information technology as a medium in official correspondence activities needs to be improved to enhance the efficiency and effectiveness of service at Economics Faculty not only for the head of the faculty, but also the lecturers, the employees, and the college students. The implementation of e-office has to consider several factors to support as appropriate infrastructures, financial institutions, commitment, human resource, and also system maintenance to make e-office stable.     Keywords             : E-office, E-government, Official Correspondence, and Work Effectiveness.